Diagnosis and treatment of Müllerian anomalies: Experience at the Fundación HOMI - Daniela Moreno Villamizar; Paula Quintero Garzón; Tatiana Daza Ladino; Laura Daniela Pérez Daza; Maria Jose Neira; Fernando Fierro; Ivan Dario Molina Ramirez; Juan Valero (Elsevier, 2023)
Background: Müllerian anomalies are rare developmental abnormalities. In the pediatric population, they manifest clinically during puberty and may require surgical treatment for symptom management. Methods: Retrospective case series study of children with Müllerian anomalies who were taken to diagnostic or therapeutic procedures by the pediatric surgery service at the Fundación HOMI from January 2018 to October 2022. Statistical analysis was performed calculating measures of central tendency and dispersion. Results: Fifteen patients were included. The most common reason for consultation was abdominal pain in 80 % of the cases. Associated comorbidities were found in 73.3 % of the patients, the most frequent being anorectal malformations (40 %) and renal agenesis (33.3 %). Pelvis MRI was performed in all cases. the most commonly observed finding was imperforate hymen, accounting for 19.8 % of cases. The anomaly was surgically corrected in 86 % of the patients. The median age at the time of surgery was 13 years (IQR 10-14). Reoperation was required in 33.3 %, of which all required vaginoscopy and dilatation. Conclusions: Müllerian anomalies are rare and usually present with nonspecific symptoms, the most frequent being pain. They are usually associated with renal and anorectal anomalies. In this case series, the use of magnetic resonance imaging and vaginoscopy were essential for diagnosis.